Luminescence of a binuclear europium complex bearing a 4-nitrophenolate chromophore: a different way of seeing pH dependence. Issue 36 (12th April 2016) - Blackburn, Octavia A.; Tropiano, Manuel; Natrajan, Louise S.; Kenwright, Alan M.; Faulkner, Stephen
Abstract : A europium complex derived from NP-(DO3A)2 exhibits pH-dependent europium-centred luminescence following excitation of the nitrophenolate chromophore. Abstract : A europium complex derived from NP-(DO3A)2 exhibits pH-dependent europium-centred luminescence following excitation of the nitrophenolate chromophore. Such behaviour is not observed with an analogous mononuclear complex, suggesting coordination of both lanthanide ions to the phenolate oxygen in the emissive species.